A alfabetização ecológica no espaço escolar: estudos e ações ambientais voltadas ao ensino de Biologia - Nascimento, José Pedro Tavares do (2019)
The 21st Century presents us with different challenges in terms of understanding the relationship between society and nature and demands from humanity a revision of values and a profound change in the way we think and act, conditions that will only materialize through educational processes. The school environment represents, in this context, a potentially influential locus regarding the promotion of Ecological Literacy, as a process committed to the formation of subjects with planetary identity and identified with the socio-environmental dimension. This work aimed to develop, in the school context, contextualized environmental studies and interventions, guided by the Ecological Literacy applications, as pedagogical basis in the formation of subjects responsible with the environmental dimension in and out of school. The qualitative research was conducted in a School of Basic Education, in the State of Paraíba. As a pedagogical strategy, action research was adopted, based on the following aspects: apprehension of the socio-environmental context, theoretical contribution, selection of Ecology contents to be used as an intermediate and the structuring of Pedagogical Workshops. Five thematic workshops were held, mediated by active methodologies, in which the relevant knowledge was produced, associated with the development and implementation of sustainable practices and experiences, with repercussions for the school community and surrounding areas. The study, in addition to granting the status of protagonists to the participating students, made some environmental issues of daily school life visible and proposed pedagogical alternatives to address the main environmental problems in the school and in the municipality. As a didactic-pedagogical product of the activities developed, a paradidactic book guide of sustainable pedagogical practices was prepared to teach in order to complement the teaching of ecology. This paradidactic guide entitled: "Eco-literacy: studies and practices in environmental education focused on the school space", will be available to teachers of Science, Biology and related areas of Basic Education, as an instrument for guidance to classes of Environmental Education.